STRATEGI PEMERINTAH DAERAH TERKAIT PENCEGAHAN ISU RADIKALISME KANAN DI KABUPATEN GARUT - Rendy Adiwilaga; Syifa Davia Harija (Universitas Sultan Ageng Tirtayasa, 2018)
Recently, the ideology of Islamist militant to build a nation under Islamic government appears to give impact both politically and socially to the society. Garut, in this case, historically had known as the hideout of DI/TII and today, it is frequently selected as the hiding place of national or ‘ex middle-east’ radicalists. This study is a descriptive study that used phenomenology approach to examine how local government, namely Garut regency government, as the stickholder acts to protect civilians and maintain regional stability. This study also covers discussion of the strategy they had used to prevent radicalism. Findings show that local government, in this case the Garut regency government, only applied ceremonial strategy to anticipate the act of radicalism in their region. In the other words, they have not made any real move to prevent radicalism yet. Keywords: Strategy, Local Government, Radicalism